Guide :

# What is 1/3 minus 3/10 simplified

What is 1/3 minus 3/10 simplified

## Research, Knowledge and Information :

### 3 5/9 minus 2 1/6 simplified - Brainly.com

3 5/9 minus 2 1/6 simplified 2. Ask for details ; Follow; ... 1 7/18 3 5/9 equals 3 10/18 and 2 1/6 is equal to 2 3/18 so 3 10/18 minus 2 3/18 equals 1 7/18 Comments ...

### Simplifying Fractions - Math Is Fun

Simplifying Fractions. To simplify a fraction, divide the top and bottom by the highest number that ... Likewise we can't divide evenly by 3 (10/3 = 3 1 3 and also 35 ...

### 8 1/3 minus 4 3/4 =?? Keep it simple (not simplified) DO NOT ...

8 1/3 minus 4 3/4 =?? Keep it simple (not simplified) DO NOT DELETE ... First find the least common denominator of 1/3 and 3/4. 1/3= 4/12 and 3/4=9/12. 8 4/12 minus 4 ...

### Fractions - Engrade Wikis - McGraw Hill Education

Answers (sums; differences; quotients; products) that are improper must be simplified. Ex. 1: 3/4 + 3/4 = 6/4. ... (see simplifying improper fractions). 23/21 = "1 2 ...

### Can square root of 10 be simplified? | Socratic

Can square root of 10 be simplified? ... Is there a way to put a plus minus sign in an answer? Soc If the radius of a circle is tripled, how does the ...

### Simplifying with Parentheses (page 1 of 3) - Purplemath

Simplifying with Parentheses (page 1 of 3) This ... (x – 3) I have to take the "minus" through the parentheses. ... "–1x + 3" as not fully simplified.

### NumberNut.com: Fractions and Decimals: Fractions: Subtraction 1

... 4/21 cannot be simplified. You are done. Answer: 1/3 ... so let's just multiply by equivalents of 1 to create two new equivalent fractions: 4/5 = 4/5 * 1 = 4/5 ...

### Fraction calculator with steps: 3 1/8 + 2 3/8 - 1 1/4

... calculation: 3 1/8 + 2 3/8 ... Fraction calculator with steps. ... Plus + is addition, minus sign -is subtraction and ()[] ...

### Simplifying rational expressions (advanced) (article) | Khan ...

Simplifying rational expressions (advanced) ... does not equal, 3, comma, minus, 1. The simplified expression must have the same undefined values. ...

## Suggested Questions And Answer :

### how can I simplify the last problem

26r-2=3r^2. We need to put this into standard form. The standard quadratic form is ax^2+bx+c=0, where x is the unknown and a, b and c are numbers. The unknown is r in this problem, rather than x, so let's put the equation into quadratic form: 3r^2-26r+2=0. How did I get this? Subtract 26r from each side: -2=3r^2-26r. Now, add 2 to each side: 0=3r^2-26r+2, which is the same as 3r^2-26r+2=0. (There's no mystery here. The equals sign shows us that we have equality of quantity. If, for example, an apple cost 30 cents or pennies, then 30 cents will buy an apple, so we can say apple=30 or 30=apple.) This equation doesn't factorise, so we need the formula to solve it: r=(26+sqrt(26^2-4*3*2))/6 (this is the quadratic formula x=(-b+sqrt(b^2-4ac))/2a. All I've done is put b=-26, a=3 and c=2 into the formula. The plus-or-minus sign (+) means there are two answers, one using plus and the other using minus.) So r=(26+sqrt(676-24))/6=(26+sqrt(652))/6=8.589 or 0.0776. Because b=-26, -b=26: that's why the minus has disappeared. I hope the extra info helps you to understand.

### Can you simplify it step by step as well

Answered earlier: 26r-2=3r^2. We need to put this into standard form. The standard quadratic form is ax^2+bx+c=0, where x is the unknown and a, b and c are numbers. The unknown is r in this problem, rather than x, so let's put the equation into quadratic form: 3r^2-26r+2=0. How did I get this? Subtract 26r from each side: -2=3r^2-26r. Now, add 2 to each side: 0=3r^2-26r+2, which is the same as 3r^2-26r+2=0. (There's no mystery here. The equals sign shows us that we have equality of quantity. If, for example, an apple cost 30 cents or pennies, then 30 cents will buy an apple, so we can say apple=30 or 30=apple.) This equation doesn't factorise, so we need the formula to solve it: r=(26+sqrt(26^2-4*3*2))/6 (this is the quadratic formula x=(-b+sqrt(b^2-4ac))/2a. All I've done is put b=-26, a=3 and c=2 into the formula. The plus-or-minus sign (+) means there are two answers, one using plus and the other using minus.) So r=(26+sqrt(676-24))/6=(26+sqrt(652))/6=8.589 or 0.0776. Because b=-26, -b=26: that's why the minus has disappeared. I hope the extra info helps you to understand.

### Simplify 2n to the second power minus 4n times 5n minus 10n to the second power plus 4

2x^2 -10x^2 +4x+4=0 bekum -8x^2 +4x+4=0 or +8x^2 -4x -4=0...bekum 2x^2 -x -1=0 quadratik equashun giv (x-1)*(x+0.5)=0 or roots=1 & -0.5

### How would I simplify 11^-5 x 11 ^ -3 ?

Because 11 is common to both terms, multiply means add the exponents: 11^(-5+(-3))=11^(-5-3) or 11^-(5+3)=11^-8. Same applies to -2: -(-2)^(0+3-4-3) (because divide means subtract just as multiply means add). -(-2)^(-4) is the result of combining the exponents. Even exponents turn the minus in front of the 2 into plus: -(2)^(-4). Minus in an exponent means reciprocal: -1/2^4=-1/16, because 2 to the power 4 is 16. Note how the leading minus sign stays all the way through.

### how to solve -4/9(2x-4)=48

Is this -4/(9(2x-4))=48? Or (-4/9)(2x-4)=48? We can find the answers to both questions. Let's take the first interpretation first and see what we get. To solve it we need to get rid of the fraction. In all questions of this type we take the denominator of the fraction (the bottom bit), and multiply both sides of the equation by it, which is the same as taking it across the equals sign from left, where it was a divisor over to the right, where it becomes a multiplier. So we get -4=48*9(2x-4). We have the unknown x inside the brackets, so we have to get it out into the open by multiplying what's outside by everything in the brackets. That gives us -4=864x-1728. Already this looks like the wrong interpretation of the question because the numbers are big and clumsy. But we'll carry on. The next thing to do is get the knowns (ordinary numbers) on one side of the equals and the unknowns on the other. So -1728 on the right becomes +1728 when we take it across to the left (because the equals sign changes + to - and - to +, multiply to divide and divide to multiply). When we add 1728 to -4 it's the same as subtracting 4 from 1728, so we get 1724=864x. So we take 864 from right to left (changing multiply to divide as we move it) and we get 1724/864=x, which gives us a horrible 431/216 or 1.995 approx. seems unlikely then that this was the intended question. Let's go for the other interpretation: (-4/9)(2x-4)=48. One thing to notice (which also applied to the first interpretation) is that  the equation can be simplified by dividing both sides by 4. So (-1/9)(2x-4)=12. The only fraction we have is -1/9, so we just need to take the 9 across to the right where it multiplies 12. Therefore -(2x-4)=108. We can simplify this because 2 divides into both sides of the equation. So we get -(x-2)=54.  We can take the brackets with the minus sign over to the other side of the equation where the minus will become plus. So we get 0=54+x-2. Now we separate the knowns from the unknowns. -54+2=x. So x=-52. This looks more like the correct interpretation.

### find the number of red, blue and yellow stars that are in the bag

R + B = Y B^2 = R B^2 + R = Y + 12 Y/B = R - 11 B^3 = 4Y - R Look at these this line: B^2 = R In the other lines replace all Rs with B^2: B^2 + B = Y B^2 + B^2 = Y + 12 Y/B = B^2 - 11 B^3 = 4Y - B^2 Let's re-word the third line: B^2 + B = Y B^2 + B^2 = Y + 12 Y = B^3 - 11B B^3 = 4Y - B^2 See the first line?  Let's replace all of the Ys with B^2 + B: B^2 + B^2 = B^2 + B + 12 B^2 + B = B^3 - 11B B^3 = 4(B^2 + B) - B^2 Simplify: 2B^2 = B^2 + B + 12 B^2 = B^3 - 12B B^3 = 4B^2 + 4B - B^2 More simplifying: B^2 = B + 12 B^2 = B^3 - 12B B^3 = 3B^2 + 4B Consider the first line: B^2 = B + 12 Move everything to one side: B^2 - B - 12 = 0 Same as: (B - 4) (B + 3) = 0 B has to equal 4 or -3. You can't have negative 3 of a thing, so B = 4 Consider the other two lines: B^2 = B^3 - 12B B^3 = 3B^2 + 4B Check those to make sure B = 4 works. 4^2 = 4^3 -12*4 >> 16 = 64 - 48 >> Yes. 4^3 = 3*4^2 + 4*4 >> 64 = 48 + 16 >> Yes. Remember how we said B^2 + B = Y ?  Now that we know B = 4, we can do this: 4^2 + 4 = Y 16 + 4 = Y Y = 20 Remember how we said B^2 = R ?  Now that we know B = 4, we can do this: 4^2 = R R = 16 Answer:  16 red, 4 blue, 20 yellow.

### Simplify each expression 5x-3y-2x+3y

you can combine all the y terms and all of the x terms 5x minus 2x is 3x -3y+3y is 0 simplified version of this is 3x

### Rolles theorem on f(x) = Xsqrt(64-X^2) on the interval [-8,8]?

your derivative should have been sqrt(64-x^2) - x^2/sqrt(64-x^2) The minus sign coming from the derivative of (-x^2) Setting the derivative to zero, sqrt(64-x^2) - x^2/sqrt(64-x^2) = 0   multiply both terms by sqrt(64 - x^2) (64 - x^2) - x^2 = 0 64 = 2x^2 32 = x^2 x = +/- 4.sqrt(2) Answer: option b

### sqrt(3a+10) = sqrt(2a-1) + 2

sqrt(3a+10)=sqrt(2a-1)+2 To remove the radical on the left-hand side of the equation, square both sides of the equation. (~(3a+10))^(2)=(~(2a-1)+2)^(2) Simplify the left-hand side of the equation. 3a+10=(~(2a-1)+2)^(2) Squaring an expression is the same as multiplying the expression by itself 2 times. 3a+10=(~(2a-1)+2)(~(2a-1)+2) Multiply each term in the first group by each term in the second group using the FOIL method. FOIL stands for First Outer Inner Last, and is a method of multiplying two binomials.  First, multiply the first two terms in each binomial group.  Next, multiply the outer terms in each group, followed by the inner terms.  Finally, multiply the last two terms in each group. 3a+10=(~(2a-1)*~(2a-1)+~(2a-1)*2+2*~(2a-1)+2*2) Simplify the FOIL expression by multiplying and combining all like terms. 3a+10=(~(2a-1)^(2)+4~(2a-1)+4) Remove the parentheses around the expression ~(2a-1)^(2)+4~(2a-1)+4. 3a+10=~(2a-1)^(2)+4~(2a-1)+4 Raising a square root to the square power results in the expression inside the root. 3a+10=(2a-1)+4~(2a-1)+4 Add 4 to -1 to get 3. 3a+10=2a+3+4~(2a-1) Since a is on the right-hand side of the equation, switch the sides so it is on the left-hand side of the equation. 2a+3+4~(2a-1)=3a+10 Move all terms not containing ~(2a-1) to the right-hand side of the equation. 4~(2a-1)=-2a-3+3a+10 Simplify the right-hand side of the equation. 4~(2a-1)=a+7 Divide each term in the equation by 4. (4~(2a-1))/(4)=(a)/(4)+(7)/(4) Simplify the left-hand side of the equation by canceling the common terms. ~(2a-1)=(a)/(4)+(7)/(4) To remove the radical on the left-hand side of the equation, square both sides of the equation. (~(2a-1))^(2)=((a)/(4)+(7)/(4))^(2) Simplify the left-hand side of the equation. 2a-1=((a)/(4)+(7)/(4))^(2) Combine the numerators of all expressions that have common denominators. 2a-1=((a+7)/(4))^(2) Expand the exponent of 2 to the inside factor (a+7). 2a-1=((a+7)^(2))/((4)^(2)) Expand the exponent 2 to 4. 2a-1=((a+7)^(2))/(4^(2)) Simplify the exponents of 4^(2). 2a-1=((a+7)^(2))/(16) Multiply each term in the equation by 16. 2a*16-1*16=((a+7)^(2))/(16)*16 Simplify the left-hand side of the equation by multiplying out all the terms. 32a-16=((a+7)^(2))/(16)*16 Simplify the right-hand side of the equation by simplifying each term. 32a-16=(a+7)^(2) Since (a+7)^(2) contains the variable to solve for, move it to the left-hand side of the equation by subtracting (a+7)^(2) from both sides. 32a-16-(a+7)^(2)=0 Squaring an expression is the same as multiplying the expression by itself 2 times. 32a-16-((a+7)(a+7))=0 Multiply -1 by each term inside the parentheses. 32a-16-a^(2)-14a-49=0 Since 32a and -14a are like terms, add -14a to 32a to get 18a. 18a-16-a^(2)-49=0 Subtract 49 from -16 to get -65. 18a-65-a^(2)=0 Move all terms not containing a to the right-hand side of the equation. -a^(2)+18a-65=0 Multiply each term in the equation by -1. a^(2)-18a+65=0 For a polynomial of the form x^(2)+bx+c, find two factors of c (65) that add up to b (-18).  In this problem -5*-13=65 and -5-13=-18, so insert -5 as the right hand term of one factor and -13 as the right-hand term of the other factor. (a-5)(a-13)=0 Set each of the factors of the left-hand side of the equation equal to 0. a-5=0_a-13=0 Since -5 does not contain the variable to solve for, move it to the right-hand side of the equation by adding 5 to both sides. a=5_a-13=0 Set each of the factors of the left-hand side of the equation equal to 0. a=5_a-13=0 Since -13 does not contain the variable to solve for, move it to the right-hand side of the equation by adding 13 to both sides. a=5_a=13 The complete solution is the set of the individual solutions. a=5,13

### how to solve for x with fractions

Simplifying x3 + 3x2 + -4x = 0 Reorder the terms: -4x + 3x2 + x3 = 0 Solving -4x + 3x2 + x3 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), 'x'. x(-4 + 3x + x2) = 0 Factor a trinomial. x((-4 + -1x)(1 + -1x)) = 0 Subproblem 1 Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0 Subproblem 2 Set the factor '(-4 + -1x)' equal to zero and attempt to solve: Simplifying -4 + -1x = 0 Solving -4 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + -1x = 0 + 4 Combine like terms: -4 + 4 = 0 0 + -1x = 0 + 4 -1x = 0 + 4 Combine like terms: 0 + 4 = 4 -1x = 4 Divide each side by '-1'. x = -4 Simplifying x = -4 Subproblem 3 Set the factor '(1 + -1x)' equal to zero and attempt to solve: Simplifying 1 + -1x = 0 Solving 1 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1x = 0 + -1 -1x = 0 + -1 Combine like terms: 0 + -1 = -1 -1x = -1 Divide each side by '-1'. x = 1 Simplifying x = 1 Solution x = {0, -4, 1}